Human vs. Automated Sales Agents: How and Why Customer Responses Shift Across Sales Stages - Adam, Martin; Roethke, Konstantin; Benlian, Alexander (Information Systems Research, 2023)
Customers in sales processes increasingly encounter automated sales agents that complement or replace human sales agents. Yet, little is known about whether, how, and why customers respond to automated agents in contrast to human agents across successive decision stages of the same sales process. Even less is known about customer responses to combinations where both agents assume distinct roles and focus on complementary tasks that are traditionally performed by only one single agent. Against this backdrop, this paper explores the influence of increasingly common sales representative types on customer decisions across sales stages. Our findings demonstrate that customer responses to automated (versus human) sales agents are not stable in sales processes and instead, shift as customers move across sales stages. What is more, the paper shows that combinations of sales agents versus single sales agents do matter, yet their differential effects depend on contextual features of the sales setting. These insights are important because vendors may assume that a certain type of sales agent is always more appreciated by customers, whereas in fact, different sales agent types bring distinct attributes to the table, and customers’ appreciation of these attributes shifts across sales stages.